Genetic diversity comparison among invasive fish populations (Nemipterus randalli and Serranus cabrilla) from Mediterranean and Red Sea coastal waters using cytochrome c oxidase subunit I (COI) - Ogwang, Joel (AUC Knowledge Fountain, 2019)
Since the Suez Canal connected the Red Sea with the Mediterranean, several fish species have migrated between the two seas. Nemipterus randalli has crossed from the Red Sea to the Mediterranean (Lessepsian migration) whereas Serranus cabrilla is considered to have crossed in the reverse direction (anti-Lessepsian migration). Genetic variation between populations of these fish species on either side of the Suez Canal might provide valuable information on their patterns of migration. In this study, 600 bp of cytochrome c oxidase subunit I (COI) sequences were used to compare genetic diversity of populations of N. randalli from the eastern Mediterranean with a population off the Red Sea coast near Hurghada, Egypt. For comparison, three other Nemipterus species were included. Similarly, genetic diversity of Serranus cabrilla from the Gulf of Suez was compared with populations in the eastern Mediterranean Sea. A Maximum Likelihood (ML) tree was constructed using Molecular Evolutionary Genetics Analysis version 7 (MEGA7) software to visualize the evolutionary relationships of S. cabrilla and Nemipterus species of the two seas. Population structures of N. randalli and S. cabrilla were assessed by constructing haplotype networks using PopART. Results from COI sequence divergence analysis revealed possible existence of cryptic species of N. bipunctatus in the Red Sea. Although the ML tree resolved Nemipterus species into four clades representing the four species analyzed, all N. randalli sequences from both seas formed a single clade. Genetic diversity analysis revealed that Mediterranean populations of N. randalli share one haplotype from the Red Sea and supported unidirectional multiple invasion events from the Red Sea to the Mediterranean Sea. Meanwhile, S. cabrilla sequences formed two phylogenetic clades representing the Gulf of Suez and eastern Mediterranean Sea populations. S. cabrilla from the Gulf of Suez also had a significantly reduced sequence divergence compared to Mediterranean Sea populations. In addition, none of the 17 haplotypes in the Mediterranean Sea was found among the 12 haplotypes in the Gulf of Suez. Together, these results provided evidence that the S. cabrilla population in the Gulf of Suez did not come from the Mediterranean Sea through the Suez Canal as was previously thought. According to these results, reported cases of invasion on either side of the Suez Canal should be followed by genetic investigations on a species-by-species basis.